Aluminum Thin Film on Various Substrates using Magnetron Sputtering - Saidon, Nur Aqilah; Mohamed Ali, Riyaz Ahmad (Evolution in Electrical and Electronic Engineering, 2023)
Many sectors employ aluminum (Al) thin films, however further study is required to improve their value and performance. In order to achieve the necessary qualities, these films are made that use deposition processes such as physical vapour deposition, chemical vapour deposition, and electrochemical deposition. Al thin films have properties like structure, electrical conductivity, optical conduct, mechanical stability, and adhesion strength that can be improved by alloying, using new deposition techniques, patterning, integrating them into devices, conducting stability studies, and taking cost-effectiveness into account. The purpose of this experiment is to determine the conductivity, morphology, topology, and thickness of the Al thin film on various substrates, in order to compare which substrates offered the better results. Studying these aspects will help Al thin film technology improve for a variety of applications. The use of aluminum (Al) thin films in semiconductors, optoelectronic, and energy storage applications is substantial, and further study is required to improve their functionality and look into new integration opportunities in advanced technologies. In conclusion, the FTO glass substrates offer good electrical conductivity, thickness, morphology, and topology compared to Si wafers.